Outcomes of Reservation Policy Implementation in Armed Police Force, Nepal - Thapa Magar, Ananda; Katel, Bibhuti (Journal of APF Command and Staff College, 2023)
Nepal adopted the reservation policy with the motive to ensure the participation of women and marginalized groups through the Interim Constitution, 2007 and the Constitution of Nepal 2015. APF, Nepal has adopted the reservation system in the recruitment process as a government institution. However, it is necessary to understand the outcome of the reservation on its overall recruitment policy, which this article has tried to explore. This article adopted an analytical approach based on both primary and secondary sources of data. In Nepal, due to its social structure, diversity, and historical marginalization, reservation ensures equal participation, provides opportunities for socio-economic development, and represents marginalized communities. The reservation policy has been instrumental in making the APF in Nepal an inclusive force. The findings suggested that APF, Nepal should develop a time-bound reservation policy and revise it at regular intervals. The study did not find instances where the APF was forced to recruit incompetent personnel due to the reservation policy. On the contrary, reservists have performed well, with some even receiving national recognition for their contributions. Regular reviews of the policy are recommended to enhance the effectiveness of reservation policies in the future. Additionally, community upliftment through development programs focused on education and reservations based on economic capabilities were identified.